Análise do potencial da osteopontina e da Serpina1 como biomarcadores do carcinoma epidermóide de cabeça e pescoço - Figuera Gómez, Celeny Milagros (2017)
Head and neck squamous cell carcinoma (HNSCC) is the most frequent histological type of head and neck cancers. Despite the numerous studies, a common set of biomarkers for HNSCC has not been established yet, evidencing the necessity to find molecules that facilitate the prognosis and early diagnosis of this disease. The objective of this research was to evaluate the Serpine1 and Osteopontin (OPN) as biomarkers in HNSCC because they are poorly evaluated molecules in this cancer. Biological samples and clinical-pathological data were collected from 40 patients with HNSCC and 11 healthy individuals. The detection of Serpina1 and OPN mRNA expression was performed by qPCR trials on tumor tissues and normal tissue samples. The evaluation of Serpina1 and OPN protein expression was performed with serum from both HNSCC patients and a control group by Western blotting. A significant increase in Serpina1 mRNA was observed in tumor tissue compared to normal tissue (p=0.0014) and in relation to different clinical-pathological characteristics evaluated (sex, smoking and smoking, staging and lymph node development). Serpina1 protein expression was also elevated in patients with HNSCC in relation to controls (p=0.0007) and in clinical-pathological characteristics evaluated. For OPN, no relevant significant differences were found for mRNA and protein except OPN protein expression, which was shown higher in the advanced stage (III/IV) (p=0.0181). Serpina1 has been shown as a potential biomarker of HNSCC for alterations found in tumor tissue and blood, which may facilitate its application in the development of the disease. The OPN should be better evaluated to establish the possible significant differences.